Pengaruh Kemampuan Negosiasi, Kompetensi, dan Independensi Terhadap Kualitas Audit: Studi Empiris pada Auditor Internal Inspektorat Kota Tual Provinsi Maluku - Muhammad Iman Fatardha; Murtanto Murtanto (Ikatan Da'i Indonesia, 2026)
This study aims to determine the effects of: (1) Negotiation Skills on Audit Quality, (2) Competence on Audit Quality, and (3) Independence on Audit Quality. This research is classified as associative research. The population in this study consisted of 32 internal auditors working at the Inspectorate of Tual City, Maluku Province. The data analysis techniques used were simple linear regression analysis and multiple linear regression analysis. The statistical tool used was SPSS 16.0 for Windows. The results of this study indicate that Negotiation Skills, Competence, and Independence have a positive effect on Audit Quality.